Investigating Live Worksheets as Assessment Tool for Senior High School Students - Kholida, Firda; Rohmana, Wahyu Indah Mala; Sa'diyah, Khalimatus (Prodi Pendidikan Bahasa Inggris, FPBS, Universitas PGRI Semarang, 2025)
Live Worksheets, a technology-based tool that helps educators in assessing student performance, is one of the tools that facilitate teachers in designing electronic worksheets or known as E-LKPD. Live Worksheets allows teachers to easily create and manage electronic worksheets (E-LKPD) that are more interactive and dynamic compared to conventional E-LKPD which are usually printed and less flexible in terms of interactivity and content updates. In addition, the objectives of this study are to discover (1) the implementation of using Live Worksheets, (2) the perceptions of the teacher and students of Live Worksheets as assessment tool, and (3) the difficulties experienced by teacher when using Live Worksheets as an assessment tool. The method used is descriptive quantitative method by conducting observations, distributing questionnaires, and conducting semi-structured interviews. The participants in this study were one teacher and class XI IPS III which totaled 34 students. The results of this study showed that the implementation of Live Worksheets by teacher is done by distributing the available worksheets to students. The teacher's perspective on Live Worksheets is very positive because this tool is considered easy to use, effective, has good question quality, offers flexibility, facilitates grade management, is efficient, and provides good feedback. The majority of students also had a positive view of the tool. The perceptions are divided into three categories, familiarity and ease of use, learning experience and motivation, also effectiveness and skill improvement. The challenges are academic dishonesty, managing the behavior of very active students, and also designing her own worksheets. It is suggested that teachers utilize Live Worksheets’ features to create tailored materials, and students engage with integrity to optimize learning.